2002
DOI: 10.1076/apab.110.1.54.910
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Effects on Secretion from Subsets of Lactotrophs: Role of Folliculo-Stellate Cells and Annexin 1

Abstract: Prolactin secretion is controlled by the hypothalamus, and by circulating steroids; oestrogens stimulate, but glucocorticoids inhibit prolactin release. Lactotrophs express intracellular receptors for oestrogens, but apparently not glucocorticoids. Therefore, a genomic effect of oestrogens could be direct, but that of glucocorticoids appears to be indirect. Lactotrophs are not a homogeneous cell population: some have large irregular dense-cored vesicles, others have small round vesicles, but the functional sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…In addition, PKC blockade prevented the dexamethasoneinduced translocation of ANXA1 to the cell surface, a step we believe is critical to the putative paracrine action of ANXA1 in the anterior pituitary gland (3,4,11). While our data clearly demonstrate that ANXA1 exported from the pituitary cells is serine phosphorylated, we cannot exclude the possibility that the transport system, which may involve ATP-binding cassette transporter proteins (56), is regulated by PKC. First, that the steroid-induced activation of PKC causes serine/threonine phosphorylation of ANXA1 and that the phosphorylated protein is a substrate for the transporter system; it is thus translocated to the pericellular compartment where it exerts its regulatory actions on peptide release.…”
Section: Role Of Pkccontrasting
confidence: 54%
“…In addition, PKC blockade prevented the dexamethasoneinduced translocation of ANXA1 to the cell surface, a step we believe is critical to the putative paracrine action of ANXA1 in the anterior pituitary gland (3,4,11). While our data clearly demonstrate that ANXA1 exported from the pituitary cells is serine phosphorylated, we cannot exclude the possibility that the transport system, which may involve ATP-binding cassette transporter proteins (56), is regulated by PKC. First, that the steroid-induced activation of PKC causes serine/threonine phosphorylation of ANXA1 and that the phosphorylated protein is a substrate for the transporter system; it is thus translocated to the pericellular compartment where it exerts its regulatory actions on peptide release.…”
Section: Role Of Pkccontrasting
confidence: 54%
“…The steroid thus had no effect on the evoked release of ACTH from AtT20 D1 cells cultured in isolation but readily suppressed the release of the peptide when the corticotrophs were co‐cultured with TtT/GF cells. The actions of dexamethasone were blocked by mifepristone and, thus appeared to be mediated by the glucocorticoid receptor, which is expressed in abundance in TtT/GF and primary folliculo‐stellate cells (16, 17). Interestingly, however, and in contrast to data from primary pituitary tissue, dexamethasone produced at best only partial blockade (approximately 60%) of the response to CRH even when the TtT/GF cell count was increased to 50 000 per well.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on TtT/GF and primary folliculo‐stellate cells have shown that cell surface ANXA1 is located on the cell processes and at other points where the cells make intimate contact with endocrine cells (12, 17). Thus, they raise the possibility that ANXA1 acts as a juxtacrine rather than paracrine agent.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of glucocorticoid in the anterior pituitary gland may be mediated in part by annexin-1, a member of the annexin superfamily of Ca 2+ -or phospholipid binding proteins [53]. Annexin-1 is synthesized in the pituitary folliculo-stellate cells in response to glucocorticoids, and acts on GH, PRL and ACTH cells to modulate their hormone secretion [54][55][56]. It is possible that annexin-1 mediates glucocorticoid action in the fetal pituitary gland for the induction of GH production.…”
Section: Mechanisms For Inducing Gh Expression By Glucocorticoidsmentioning
confidence: 99%